Analyzing Algebraic Operations And Properties Of Pentapartitioned Neutrosophic Binary Sets - Yoha, A. Anit; Melbha, M. Jaslin (Journal of Neonatal Surgery, 2025)
A Pentapartitioned Neutrosophic Binary Set is represented through a membership functions of truth, contradiction, ignorance, unknown, and falsity, which quantifies the degrees of membership functions for each element over two universes. This paper explores an algebraic operations defined on pentapartitioned neutrosophic binary set. The fundamental algebraic operations on pentapartitioned neutrosophic binary set namely algebraic sum, algebraic difference, algebraic product, algebraic quotient, scalar multiplication, and exponentiation. To further clarify, we include examples illustrating the implementation of the defined operations. Furthermore, these operations are also investigated for key properties, like commutativity and distributivity, and validated using mathematical proofs.